Association between periodontal disease and atherosclerosis: a bibliometric analysis - Chang, Haoxiang; Wang, Yahui; Zhang, Ziqi; Mi, Zhongqian; Qiu, Xinjie; Zhao, Miaomiao; Wang, Chong; Bai, Xue; Ren, Xiuyun (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIn recent years, the relationship between periodontal disease (PD) and atherosclerosis (AS) has garnered significant scholarly attention. Chronic inflammation induced by PD may promote the onset and progression of AS through multiple mechanisms. Given the increasing global incidence of both PD and AS, which adversely affects patients’ quality of life and longevity, further investigation into the interplay between PD and AS is of substantial clinical importance. This study aims to conduct a comprehensive analysis of the association between PD and AS using bibliometric methods.MethodsArticles and reviews on the association between PD and AS were retrieved from the Web of Science Core Collection (WOSCC) on June 1, 2023. Bibliometric and knowledge mapping analyses were conducted using CiteSpace [6.3.R1 (64-bit) Advanced].ResultsThrough a bibliometric analysis of the literature published between 2000 and 2023 on the PD-AS relationship, we identified 1,572 relevant studies. The results show a steadily increasing number of studies on this topic annually, with a significant upward trend after 2002. Keyword analysis reveals “atherosclerosis,” “periodontal disease,” “cardiovascular disease,” “Porphyromonas gingivalis,” and “periodontal pathogens” as research hotspots. Collaboration network analysis highlights the United States as the primary contributor to research in this field. Co-citation analysis shows that J Periodontol, J Clin Periodontol, and Circulation are the most frequently cited journals, reflecting their support for research in this area. Document co-citation analysis identifies several high-impact studies focusing on how systemic inflammation induced by periodontitis promotes AS. This study uncovers development trends and research hotspots in the PD-AS relationship and emphasizes the role of international collaboration and high-impact journals in advancing this field. These insights provide valuable references and guidance for future research.ConclusionPD and AS are global epidemics causing significant distress and imposing a substantial burden. Research on the PD-AS relationship is evolving rapidly and continues to be a critical focus. Elucidating the mechanisms linking PD and AS represents an emerging trend, providing valuable references for future studies.